If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 14 = 7x + 17 Reorder the terms: 14 + 11x = 7x + 17 Reorder the terms: 14 + 11x = 17 + 7x Solving 14 + 11x = 17 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 14 + 11x + -7x = 17 + 7x + -7x Combine like terms: 11x + -7x = 4x 14 + 4x = 17 + 7x + -7x Combine like terms: 7x + -7x = 0 14 + 4x = 17 + 0 14 + 4x = 17 Add '-14' to each side of the equation. 14 + -14 + 4x = 17 + -14 Combine like terms: 14 + -14 = 0 0 + 4x = 17 + -14 4x = 17 + -14 Combine like terms: 17 + -14 = 3 4x = 3 Divide each side by '4'. x = 0.75 Simplifying x = 0.75
| 3x+12y=62 | | 9x-10=10x+9 | | 72x^3+21x^6+49x^9= | | 5y=-14-49 | | x+26y=24 | | 59/22 | | 25x-6=35x+2 | | 76m+60= | | x/2=11-8 | | -9(n-7)=9-8n | | 23.5*35= | | 0.05*1.3= | | 2(2x-4)=9-2(x-1) | | 5.05-(1.55+0.05x)=0 | | t(t+4)-1=t(t+2)+3 | | 7x-10=10x+11 | | 4x^2-7x+18=6x+8 | | 32n+9=12n+17 | | x^2+11x+17=3x+2 | | 2log(2-x)=-x | | 11x-17=3x+9 | | 9u+6+5=4u-4 | | 3tanx=3.2 | | 2(5+2x)=18 | | 1/cos3x-tanx | | 3cosx-sin2x/cos2x | | 158/50 | | 5b+4a= | | x^2+3x=30 | | n+1.5=70 | | a^8b/ab^4 | | x^2+15x+31=4x+3 |